Development of preference and spontaneous recovery in choice behavior with concurrent variable-interval schedules - Mazur, James E (Animal Learning & Behavior, 1995)
Pigeons pecked on two response keys that delivered reinforcers on a variable-interval schedule. The proportion of reinforcers delivered by one key was constant for a few sessions and then changed, and subjects' choice responses were recorded during these periods of transition. In Experiment 1, response proportions approached a new asymptote slightly more slowly when the switch in reinforcement proportions was more extreme. In Experiment 2, slightly faster transitions were found with higher overall rates of reinforcement. The results from the first session, after a switch in the reinforcement proportions, were generally consistent with a mathematical model that assumes that the strength of each response is increased by reinforcement and decreased by nonreinforcement. However, neither this model nor other similar models; predicted the `'spontaneous recovery” observed in later sessions: At the start of these sessions, response proportions reverted toward their preswitch levels. Computer simulations could mimic the spontaneous recovery by assuming that subjects store separate representations of response strength for each session, which are averaged at the start of each new session.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/157-089-996-996-706 tex.type: [object Object]
Keywords: animal behavior; article; decision making; dept.psy; mathematical model; nonhuman; pigeon; reinforcement